Calculating electric power and energy generated in small wind turbine-generator sets in very short-term horizon - Parol Mirosław; Arendarski Bartłomiej; Parol Rafał (E3S Web of Conferences, 2019)
The issue of very short-term forecasting of power generated in renewable energy sources, including small wind turbine-generator sets, is getting more and more important. Because it is crucial/necessary to ensure reliable electricity supplies to consumers, it is a subject of a great significance in small energy micro-systems, which are commonly called microgrids. Small wind turbine-generator sets will be shortly characterized in this paper. Further on, typical characteristics of power generated by these units, dependent on the wind velocity, will be presented. Then results of sample calculations of electric power and energy generated by several wind turbine-generator sets of small installed capacity, in relation to the wind velocity and time intervals assumed for calculations, will be presented. On the basis of these calculations, estimation errors resulting from the magnitude of time intervals, assumed in the process of wind velocity averaging, will be determined. Some qualitative analysis of obtained estimates of electric powers and energies, in context of very short-term forecasts of these quantities, will be carried out. At the end of the paper observations and conclusions concerning analyzed subject, i.e. calculating the electric power and energy generated in small wind turbine- generator sets in a very short-term horizon, will be provided.